COSTUMBRES Y TRADICIONES ANCESTRALES PARA EL DESARROLLO TURISTICO DE LA COMUNA CHIGUILPE, EN LA PROVINCIA DE SANTO DOMINGO DE LOS TSACHILAS, AÑO 2022. - Gutiérrez Calderón, Roxana Katherine (2022)
This research is focused on tourism development in the Tsáchila de Chiguilpe commune, in which each of its customs and traditions that have their own style and are born from them, such as their clothing, gastronomy, folklore, dances, rituals, will be announced. among others, in the community of Chiguilpe they show a very colorful nature not only because of its flora and fauna, but also because they use the same nature for their clothing and handicrafts that they make themselves and present to the tourists who come to the place so that they can take a souvenir with them. On the other hand, the lack of interest in the preservation of culture, which is one of the main problems of this community, will be investigated. It should be emphasized that the ancestors have tried to maintain their culture for a long time, but it has been affected by a effect called syncretism, especially in the new generations since they are losing their cultural identity including ancestral knowledge due to the decrease in its practices and that is transcendental to develop tourism, likewise the customs and traditions of the Tsáchila commune contribute to the tourism of the Province, but the lack of management by the authorities by not facilitating access to this place makes many tourists decide to opt for other options. In the surveys carried out in the investigation, the solution to the existing problems is sought, preparing meetings for people from the surroundings of the community and the community, implementing talks in the educational units so that they know about the customs and traditions and the importance of preserve their cultural identity.